The Oxford handbook of Descartes and Cartesianism - Kolesnik-Antoine, Delphine; Nadler, Steven M. 1958-; Schmaltz, Tad M. 1960- (Oxford, United Kingdom Oxford University Press, 2019)
The Oxford Handbook of Descartes and Cartesianism comprises fifty specially written chapters on Rene Descartes (1596-1650) and Cartesianism, the dominant paradigm for philosophy and science in the seventeenth century, written by an international group of leading scholars of early modern philosophy. The first part focuses on the various aspects of Descartes's biography (including his background, intellectual contexts, writings, and correspondence) and philosophy, with chapters on his epistemology, method, aetaphysics, physics, mathematics, moral philosophy, political thought, medical thought, and aesthetics. The chapters of the second part are devoted to the defense, development and modification of Descartes's ideas by later generations of Cartesian philosophers0in France, the Netherlands, Italy, and elsewhere. The third and final part considers the opposition to Cartesian philosophy by other philosophers, as well as by civil, ecclesiastic, and academic authorities. This handbook provides an extensive overview of Cartesianism - its doctrines, its legacies and its fortunes - in the period based on the latest research.
Philosopher defying the philosophers : Descartes's life and works / Han van Ruler -- What Descartes read : his intellectual background / Roger Ariew -- Descartes's correspondence and correspondents / Theo Verbeek, Erik-Jan Bos -- Descartes on the method of analysis / Lex Newman -- Descartes's metaphysics / Lawrence Nolan -- Mind and psychology in Descartes / Gary Hatfield -- Descartes's mechanical but not mechanistic physics / Helen Hattab -- Descartes's mathematics / Sébastien Maronne -- Descartes and medicine / Gideon Manning -- Descartes on freedom / C.P. Ragland -- Descartes and the passions / Denis Kambouchner -- Descartes's philosophical theology / Igor Agostini -- Descartes's moral philosophy / Laurence Renault -- Descartes, politics, and "true human beings" / Delphine Antoine-Mahut -- The Compendium Musicae and Descartes's aesthetics / Frédéric de Buzón -- Mersenne : questioning Descartes / Claudio Buccolini -- Princess Elisabeth of Bohemia as a Cartesian / Lisa Shapiro -- Claude Clerselier and the development of Cartesianism / Tad M. Schmaltz -- Louis de La Forge on mind, causality, and union / Philippe Drieux -- "He has created a schism in philosophy" : the Cartesianism of Géraud de Cordemoy / Fred Ablondi -- Antoine Arnauld : Cartesian philosopher? / Denis Moreau -- The ambiguities of Malebranche's Cartesianism / Jean-Christophe Bardout -- The prince of Cartesian philosophers : Pierre-Sylvain Régis / Antonella Del Prete -- Jacques Rohault and Cartesian experimentalism / Mihnea Dobre -- Robert Desgabets and the supplement to Descartes's philosophy / Tad M. Schmaltz -- The early Dutch reception of Cartesianism / Wiep van Bunge -- The curious case of Henricus Regius / Tad M. Schmaltz -- Geulincx and the Quod Nescis principle : a conservative revolution / Andrea Sangiacomo -- Johannes Clauberg and the search for the Initium Philosophiae : the recovery of (Cartesian) metaphysics / Alice Ragni -- What is Cartesianism? : Fontenelle and the subsequent construction of Cartesian philosophy / Mitia Rioux-Beaulne -- Cartesianism in Britain / Sarah Hutton -- "Italy did not want to be Cartesian" : and for good reason / Giulia Belgioioso -- The creation of eternal truths : issues and context / Dan Arbib -- Cartesianism and Eucharistic physics / Jean-Robert Armogathe -- Cartesianism and feminism / Marie-frédérique Pellegrin -- Pascal and Port-Royal / Hélène Bouchilloux -- Gassendi as critic of Descartes / Antonia LoLordo -- Optics, first philosophy, and natural philosophy in Hobbes and Descartes / Douglas Jesseph -- Henry More, supporter and opponent of Cartesianism / Jasper Reid -- Cavendish vs. Descartes on mechanism and animal souls / Hadley Cooney -- Spinoza, Descartes, and the "stupid Cartesians" / Steven Nadler -- Simon Foucher and anti-Cartesian skepticism / Michael W. Hickson -- Locke on Cartesian bodies and Cartesian souls / Philippe Hamou -- Anne Conway's response to Cartesianism / Christia Mercer -- Leibniz and Descartes / Jean-Pascal Anfray -- A Cartésien Manqué : Pierre Bayle and Cartesianism / Todd Ryan -- The condemnations of Cartesian natural philosophy under Louis XIV (1661-91) / Sophie Roux -- Pierre-Daniel Huet, skeptic critic of Cartesianism and defender of religion / Thomas M. Lennon -- Gabriel Daniel : Descartes through the mirror of fiction / Justin E.H. Smith -- Physics and metaphysics in Descartes and Newton / Andrew Janiak.
Includes bibliographical references and indexes.
Keywords: Descartes, René -- 1596-1650.; Philosophy, French -- 17th century